Competence Based Education and Training: A Tool for Enhancing Employability of Polytechnic Graduates in Zimbabwe - Mukutyu, Spencer (Advances in Social Sciences Research Journal, 2024)
This paper intends to establish the role of competence-based education and training model as a tool for enhancing graduate employability of polytechnic graduates in Zimbabwe. Industry has observed the skills deficit among young people seeking employment. It is against this background that this study seeks to interrogate the CBET curricular being offered in Polytechnics and how it can enhance graduate employability among the students. The study employed the qualitative systematic review of literature from various sources such as google scholar, Scopus, science direct. Data was analysed using thematic analysis. The findings of the study indicated that competence-based education plays a significant role in enhancing graduate employability. Furthermore, findings of this study will contribute much to the existing literature on CBET and graduate employability, providing directions for policymakers, educators, and governments. It could be concluded that the CBET education system should integrate generic skills and technical skills in preparing students for the world of work.